2009
DOI: 10.1179/136217109x449201
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic impact welding of Mg to Al sheets

Abstract: Magnesium (Mg) and aluminium (Al) alloys have been lap welded using an electromagnetic impact welding technique. Metallographic examination of the welds has revealed sound and defect free interfaces. Complete metal continuity has been observed with a characteristic wavy interface. X-ray diffraction analysis has shown no intermetallic phases and suggested that this electromagnetic technique is a solid state welding process. All the shear strength samples welded with discharge energy of 6?7 kJ failed away from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Numerical investigations performed by Uhlmann and Ziefle (2010) lead to the same conclusion. Experimental investigations and according microstructural analysis and XRD presented in Kore et al (2009b) certify that also in the case of welding aluminum to magnesium no eutectic microstructure and no intermetallic phases were found. Therefore, it is concluded that the temperatures are not high enough to cause melting, in the regarded case.…”
Section: Impulse Welded Jointsmentioning
confidence: 71%
See 1 more Smart Citation
“…Numerical investigations performed by Uhlmann and Ziefle (2010) lead to the same conclusion. Experimental investigations and according microstructural analysis and XRD presented in Kore et al (2009b) certify that also in the case of welding aluminum to magnesium no eutectic microstructure and no intermetallic phases were found. Therefore, it is concluded that the temperatures are not high enough to cause melting, in the regarded case.…”
Section: Impulse Welded Jointsmentioning
confidence: 71%
“…Here, the electrical conductivity of the workpiece in principle is high enough for direct forming, but the disadvantageous ratio of skin depth and sheet thickness requires the application of additional drivers. For the same reason aluminum drivers are applied in Kore et al (2009b), where the feasibility of electromagnetic welding of magnesium to aluminum is proved (Fig. 27).…”
Section: Impulse Welded Jointsmentioning
confidence: 99%
“…Numerical simulations considering the temperature development during electromagnetic pulse welding support this theory [7] [8]. An experimental confirmation of the absence of eutectic microstructure via microstructural analysis is given in [9]. However, other publications suggest that especially at high capacitor charging energies very locally high temperatures can lead to melting and solidification, which at least contributes to the weld formation [10] [11].…”
Section: Introductionmentioning
confidence: 91%
“…When the formation of Mg-Al intermetallics was controlled, the property of the joint was controlled as well. [10] Laser weld bonding (LWB) is a new welding technique that was put forward as an alternative to pulse laser welding and adhesive bonding. It is used to join a Mg alloy to an Al alloy successfully.…”
Section: Introductionmentioning
confidence: 99%